Diagrams support revision of prior belief in primary-school children - Koerber, Susanne; Osterhaus, Christopher; Sodian, Beate (Frontline Learning Research, 2017)
The reluctance of children to revise their prior beliefs is a prominent phenomenon in the reasoning literature. One way to facilitate belief change is offering explanations, and this study examined whether highlighting (counter)evidence with diagrams leads to belief revision to the same extent. Altogether 134 preschoolers and second-graders (5- and 7-year-olds, respectively) were presented with either counterintuitive data or explanations, both refuting a strong commonly held belief concerning the relation between two variables (e.g. eating carrots improves vision). In the explanation condition, we presented children with an explanatory underlying mechanism for the unexpected causal relation (e.g. spinach and carrots contain the same amount of vitamin A, with both improving vision). In the diagram condition, children were presented with empirical data displayed in a bar graph (non-covariation), which also disconfirmed the initial belief. In both age groups and both conditions we found significant numbers of belief revision with high certainty ratings concerning the new belief. Belief change was more pronounced in second-graders, who in addition showed significantly more changes in the diagram condition than in the explanation condition. These findings suggest that the perceptual saliency of (counter)evidence helps children to correctly evaluate hypotheses, which supports changes in their prior belief.